Effects of altitude acclimatization on pulmonary gas exchange during exercise - Bebout, D E; Story, D; Roca, J; Hogan, M C; Poole, D C; Gonzalez-Camarena, R; Ueno, O; Haab, P; Wagner, P D (Journal of applied physiology (1985), 1989)
Pulmonary gas exchange was studied in eight normal subjects both before and after 2 wk of altitude acclimatization at 3,800 m (12,470 ft, barometric pressure = 484 Torr). Respiratory and multiple inert gas tensions, ventilation, cardiac output (Q), and hemoglobin concentration were measured at rest and during three levels of constant-load cycle exercise during both normoxia [inspired PO2 (PIO2) = 148 Torr] and normobaric hypoxia (PIO2 = 91 Torr). After acclimatization, the measured alveolar-arterial PO2 difference (A-aPO2) for any given work rate decreased (P less than 0.02). The largest reductions were observed during the highest work rates and were 24.8 +/- 1.4 to 19.7 +/- 0.8 Torr (normoxia) and 22.0 +/- 1.1 to 19.4 +/- 0.7 Torr (hypoxia). This could not be explained by changes in ventilation-perfusion inequality or estimated O2 diffusing capacity, which were unaffected by acclimatization. However, Q for any given work rate was significantly decreased (P less than 0.001) after acclimatization. We suggest that the reduction in A-aPO2 after acclimatization is a result of more nearly complete alveolar/end-capillary diffusion equilibration on the basis of a longer pulmonary capillary transit time.